Does Body Size Matter for Continuous-Flow Ventricular Assist Device Implantation for Bridge to Transplantation?. (July 2018) - Ono, Minoru; Nawata, Kan; Kinoshita, Osamu; Kimura, Mitsutoshi; Yamauchi, Haruo; Minegishi, Sachito; Shimada, Shogo; Komae, Hyoue; Hoshino, Yasuhiro
Abstract : Introduction: With advancement of continuous flow ventricular assist device (Cf-VAD) technology, implantation and longer support has been becoming safer and safer. Miniaturization has also allowed us to implant cf-VAD in patients with small body size. There is still some concern about stable and safe support in patients with small body size. We sought to analyze our cf-VAD implantations for bridge to transplantation (BTT) to see if there was any difference in survival or complication rates by the body size. Material and Methods: We analyzed 148 consecutive cf-VAD implantations for BTT (age: 39.7 years, 41 females) in our hospital. Ratio of female patients was significantly higher in group S (76%) than the other 2 groups (M: 24%, L: 0%). Devices used were HeartMate II in 55, Jarvik 2000 in 43, EVAHEART in 28, DuraHeart in 21 and HVAD in 1. Jarvik 2000 was more frequently used in group S (56%). There was no biventricular VAD requirement in this group. We divided patients into 3 groups according to body surface area (BSA); group S with < 1.5m 2, group M with 1.5 to < 1.7m 2 and group L with more than 1.7m 2 . BSA in each group was 1.39m 2, 1.60m 2 and 1.80m 2 for groups S, M and L, respectively. Survival after cf-VAD implantation, pump exchange (due to pocket infection) free survival, pump exchange (due to pump thrombosis) free survival and pump exchange (due to infection or pump thrombosis) free survival were analyzed using Kaplan-Meier estimates with log-rank method for statistical analyses. Follow-up was censored at heart transplantation (HTx) or device explant due to functional recovery. Follow-up was 100% complete. Results and Discussion: There was no difference in duration of support (627 days in S, 654 days in M and 686 days in L) and post-implantation follow-up period (33.0 months in S, 28.1 months in M and 36.3 months in L). Forty-three patients underwent HTx, 6 weaned from cf-VAD due to functional recovery and 14 required device exchange due to pump thrombosis or pocket infection. There was no difference in 1, 2 and 3 year survival after cf-VAD implantation (91.7%, 88.3 %, 84.6% in group L, 91.2%, 88.6%, 88.6% in group M and 91.5%, 87.6%, 87.6% in group S). No significant differences were observed in pump exchange (due to pocket infection) free survival, pump exchange (due to pump thrombosis) free survival and pump exchange (due to infection or pump thrombosis) free survival. Pump exchange free survival at 1, 2, 3 year was: 89.7%, 84.1%, 77.3% in group L, 87.7%, 85.2%, 55.1% in group M and 91.5%, 80.1%, 74.8% in group S. Conclusion: Contemporary cf-VADs for BTT were safely implanted and managed up to 3 years in small size patients when an adequate device was chosen according to patient body size. Continued study on emerging devices in the future is mandatory to extrapolate the findings in this study to other centers and countries.